2020
DOI: 10.1016/j.adolescence.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between social anxiety and depression in youth: The moderating role of maternal major depressive disorder

Abstract: Introduction: Although social anxiety symptoms and exposure to maternal major depressive disorder (MDD) have each been conceptualized as key contributors to the development of depression symptoms in youth, these risk factors have not been integrated into a single model of risk. The current study evaluated a two-hit model of risk to determine whether the impact of social anxiety on prospective changes in youth depressive symptoms is stronger among youth exposed to maternal MDD than among those of never-depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…A number of studies have been undertaken on the psychological factors linked to depression (including mastery, self-esteem, optimism, negative self-image, current or past mental health conditions, and various other aspects, including neuroticism, brooding, conflict, negative thinking, insight, cognitive fusion, emotional clarity, rumination, dysfunctional attitudes, interpretation bias, and attachment style) [ 66 , 128 , 140 , 205 , 210 , 228 , 235 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 ,…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have been undertaken on the psychological factors linked to depression (including mastery, self-esteem, optimism, negative self-image, current or past mental health conditions, and various other aspects, including neuroticism, brooding, conflict, negative thinking, insight, cognitive fusion, emotional clarity, rumination, dysfunctional attitudes, interpretation bias, and attachment style) [ 66 , 128 , 140 , 205 , 210 , 228 , 235 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 ,…”
Section: Resultsmentioning
confidence: 99%
“…If this loneliness is not handled properly, then individuals with SAD can experience depression. Several studies explain that individuals with SAD are particularly susceptible to depression (Maleki et al, 2020;Kobezak & Gibb, 2020;Kraft & Grant, 2021). It was found that the presence of disturbances in the mindset of individuals with SAD will cause dysfunction in social communication skills and lead to major depressive disorder or MDD (Maleki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%